2017
DOI: 10.5489/cuaj.4442
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of expert and crowd-sourced review of intraoperative video for quality improvement of intracorporeal urinary diversion during robotic radical cystectomy

Abstract: Introduction: Development of uretero-ileal stricture (UIS) after robotic-assisted radical cystectomy (RARC) may be dependent on surgical technique. Video review of intraoperative technique is an emerging paradigm for surgical quality improvement. We examined whether surgeon-perceived risk of UIS or crowd-sourced assessment of robotic skill are associated with the development of UIS. Methods: We conducted a case-control study comparing the operative technique of uretero-ileal anastomoses resulting in clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 26 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…One criticism of using crowdsourcing was that the scores and results were not generalizable to the evaluation of live surgery but rather only to dry laboratories [42]. This has also been demonstrated in the world of urology, where a study found an inability of crowdsourcing and video review to predict complications associated with robot-assisted radical cystectomy [44]. Other studies have shown that blinded video assessments of a surgeon's technique correlate with patient outcomes [45].…”
Section: Crowdsourcingmentioning
confidence: 99%
“…One criticism of using crowdsourcing was that the scores and results were not generalizable to the evaluation of live surgery but rather only to dry laboratories [42]. This has also been demonstrated in the world of urology, where a study found an inability of crowdsourcing and video review to predict complications associated with robot-assisted radical cystectomy [44]. Other studies have shown that blinded video assessments of a surgeon's technique correlate with patient outcomes [45].…”
Section: Crowdsourcingmentioning
confidence: 99%